The Chile Biliary Longitudinal Study: A Gallstone Cohort. Issue 2 (16th September 2020) - Koshiol, Jill; Van De Wyngard, Vanessa; McGee, Emma E; Cook, Paz; Pfeiffer, Ruth M; Mardones, Noldy; Medina, Karie; Olivo, Vanessa; Pettit, Karen; Jackson, Sarah S; Paredes, Fabio; Sanchez, Raúl; et al.
Abstract: Gallbladder cancer (GBC) is a highly fatal cancer that can be cured through cholecystectomy if identified early. The presence of gallstones is the primary risk factor for GBC, but few people with gallstones develop GBC. A key question is what drives the development of GBC among persons with gallstones. We initiated the Chile Biliary Longitudinal Study (Chile BiLS) to address this question. From 2016 to 2019, Chile BiLS enrolled 4, 726 women aged 50–74 years with ultrasound-detected gallstones from southern-central Chile, accounting for an estimated 36% of eligible women with gallstones in the study area. The median age was 59 years; 25% of the women were Amerindian (Mapuche), 60% were obese, 25% had diabetes, and 6% had cardiovascular disease. Participants will be followed for gallbladder dysplasia or cancer for 6 years. As of April 30, 2020, over 91% of those eligible completed the year 2 follow-up visit. Data being collected include epidemiologic and sociodemographic information, anthropometric measurements, blood pressure, and tooth counts. Biosamples being taken include baseline plasma, buffy coat, red blood cells, serum, blood clot from serum, and PAXgene whole blood (PreAnalytiX GmbH, Hombrechtikon, Switzerland). Complete gallbladder sampling is conducted for most participants undergoing cholecystectomy. The Chile BiLS cohort study will increase our understanding of GBC etiology and could identify potential risk stratification and early detection strategies in high-risk areas.